2022
DOI: 10.3390/ijms23179892
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E in Cardiometabolic and Neurological Health and Diseases

Abstract: A preponderance of evidence obtained from genetically modified mice and human population studies reveals the association of apolipoprotein E (apoE) deficiency and polymorphisms with pathogenesis of numerous chronic diseases, including atherosclerosis, obesity/diabetes, and Alzheimer’s disease. The human APOE gene is polymorphic with three major alleles, ε2, ε3 and ε4, encoding apoE2, apoE3, and apoE4, respectively. The APOE gene is expressed in many cell types, including hepatocytes, adipocytes, immune cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 182 publications
0
28
0
3
Order By: Relevance
“…According to several studies, both the ApoE ɛ 2 and ɛ 4 alleles have been linked to T2DM, and the ApoE ɛ 4 allele is an independent risk factor for T2DM and cardiovascular disease, including coronary artery disease ( Alagarsamy, Jaeschke & Hui, 2022a ; Eichner et al, 2002 ). Although ApoE genetic variations, particularly in the ɛ 4 allele, have been linked to T2DM susceptibility in a number of populations, including the Chinese and Korean populations in the current study, other Thai, Chilean, Indian, Mumbai, and Rancho Bernardo Studies found no association between ApoE polymorphism and T2DM ( Jia et al, 2019 ; Oh & Barrett-Connor, 2001 ; Srirojnopkun et al, 2018 ; Pitchika et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies, both the ApoE ɛ 2 and ɛ 4 alleles have been linked to T2DM, and the ApoE ɛ 4 allele is an independent risk factor for T2DM and cardiovascular disease, including coronary artery disease ( Alagarsamy, Jaeschke & Hui, 2022a ; Eichner et al, 2002 ). Although ApoE genetic variations, particularly in the ɛ 4 allele, have been linked to T2DM susceptibility in a number of populations, including the Chinese and Korean populations in the current study, other Thai, Chilean, Indian, Mumbai, and Rancho Bernardo Studies found no association between ApoE polymorphism and T2DM ( Jia et al, 2019 ; Oh & Barrett-Connor, 2001 ; Srirojnopkun et al, 2018 ; Pitchika et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since AuNPs and their complexes with siRNA could be involved in treating brain diseases, human brain endothelial cells (HBEC-5i) were chosen to determine their toxicity. The HBEC-5i cell line was selected for this experiment because these cells can express the ApoE gene [ 37 ]. It was important to find the nontoxic or low toxic AuNP concentration for cells of the BBB and crucial in the case of tested AuNPs when considering their further testing in terms of potential delivery of siRNA to the brain.…”
Section: Resultsmentioning
confidence: 99%
“…И все же наиболее важной является функция апо Е, связанная с транспортом липопротеинов плазмы крови, в том числе с переносом холестерина из периферических тканей в печень. Белок апо Е необходим для образования различных липопротеинов плазмы, включая хиломикроны, липопротеины низкой (ЛПНП), очень низкой (ЛПОНП) и высокой (ЛПВП) плотности [5], и опосредует их клиренс, будучи лигандом для рецептора ЛПНП. Этот процесс инициируется взаимодействием основных аминокислотных остатков в рецептор-связывающем домене апо Е с отрицательно заряженными остатками в лиганд-связывающих доменах этих рецепторов с последующим эндоцитозом и внутриклеточной деградацией липопротеинов в лизосомах [5].…”
Section: Introductionunclassified
“…Белок апо Е необходим для образования различных липопротеинов плазмы, включая хиломикроны, липопротеины низкой (ЛПНП), очень низкой (ЛПОНП) и высокой (ЛПВП) плотности [5], и опосредует их клиренс, будучи лигандом для рецептора ЛПНП. Этот процесс инициируется взаимодействием основных аминокислотных остатков в рецептор-связывающем домене апо Е с отрицательно заряженными остатками в лиганд-связывающих доменах этих рецепторов с последующим эндоцитозом и внутриклеточной деградацией липопротеинов в лизосомах [5]. Таким образом, апо Е способствует поддержанию нормального уровня липидов в крови путем утилизации их избытка [6].…”
Section: Introductionunclassified
See 1 more Smart Citation